Artikel Analisis Model Akuisisi Data Terhadap Piranti Analog to Digital (ADC) - Eddy Nurraharjo; Zuly Budiarso; Edy Winarno (Jurnal Ilmiah Dinamika Teknik, 2008)
Electronics technical detecpion concept fn physical values has been developed usable Wilh a high level programming language like Borland Delphi as well us interfacing software for 'iata acquisition System that applied for integraled electronic control circuits. The unit ofdata acquisitlon usable for data values converting in visualfrom a transducer or sensor as the edge ofconlrol systems. The interface file, Invin!erface.ocx and inpout32.d/l, could be a decision maker like a mediatorfor the program, So, in this chapter, our team would be analyze a models of data acquisition for Analog to digital device Wilh one type, ADC0804. ADC0804 and Borland Delphi make for our thinking because they have some unique characteristic with S bit output dala and the capability onfree-running mode.